The participative construction of the criminal decision in democratic states ruled by the law: the guaranty of participation of the parties, through confrontation, in the composition of a fair and legitimate decision - Flávio da Silva Andrade (Revista Brasileira de Direito Processual Penal)
This article concerns a topic that is not new, but it remains current:  the participatory construction of the criminal decision in a democratic State ruled by law. Starting from the concepts of Rule of Law, of Guarantism and of Democracy, it seeks to renew the importance of the equal and dialectical participation of the parties, through the adversarial system, for the composition of a fair and legitimate criminal judicial decision. It is argued, from this perspective, that the parties should take the role of protagonists in the procedural scenario, since the decision should be built in a participatory way, i.e., based on the arguments and evidence presented, thus reducing the gaps that favor judicial discretion and decisionism. It is proposed, therefore, that the solution to the concrete case (acceptance or dismissal of the information or indictment, grant or rejection of a criminal precautionary measure, conviction or acquittal) should be elaborated with support on the contribution of the litigants, from the contrast of their arguments and of the evidence produced, in adversarial proceedings, in the regular course of the process.